Writing Resistance, Reclaiming Agency: Gender Justice and Social Transformation in Contemporary Indian Women’s Fiction (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The discourse of gender justice in Indian English fiction has emerged as a significant literary and socio-political intervention through the writings of Indian women novelists. Their narratives challenge patriarchal structures, expose socio-cultural inequalities, and foreground women’s agency within contexts shaped by caste, class, religion, sexuality, and colonial legacies. This paper examines how select Indian women writers—Arundhati Roy, Anita Nair, Bama, and Meena Kandasamy—reclaim female subjectivity and articulate possibilities of social transformation. Drawing upon feminist literary criticism, postcolonial feminism, intersectionality, subaltern studies, and gynocriticism, the study argues that these writers resist hegemonic narratives by constructing women and marginalized communities as active subjects rather than passive victims.The paper analyses The God of Small Things, Ladies Coupé, Karukku, and The Gypsy Goddess to explore the relationship between gendered oppression, caste hierarchy, institutional violence, and resistance. It further examines how family, religion, caste structures, and state power regulate women’s identities and lived experiences. Through fragmented narration, dialogic storytelling, autobiographical testimony, metafiction, and vernacular expression, these writers create alternative narrative spaces that foreground silenced voices. The study also situates these texts within contemporary feminist discussions concerning digital activism, anti-caste movements, and evolving debates on gender justice. It concludes that Indian women’s fiction continues to reshape public discourse by reclaiming agency, challenging structures of inequality, and redefining literature as a site of feminist intervention and social critique.